Simple chromogenic test for detection of adulterated milk with vegetable oil at village milk collection center- A preliminary study - HAZRA, TANMAY; SINDHAV, ROHIT G; SUDHEENDRA, CHAGANTI VENKATA KARTIKEYA; RAMAN, VIMAL M (The Indian Journal of Animal Sciences, 2021)
In the present investigation, a novel chromogenic test has been developed to ascertain the presence of vegetable oil in milk. This standardized protocol did not show any false-positive results in the genuine milk samples. Adulteration of milk with vegetable oil @ 1% level could be detected by this chromogenic test protocol. This said protocol is convenient to use in the rural dairy industry especially rural-based milk collection centers; as no costly instrument or trained manpower is required for this said test.